Top 100 most cited articles on anterior cervical discectomy and fusion - Ding, Zhiyu; Ren, Yijun; Cao, Hongqing; Li, Jinsong (Frontiers in Surgery, 2022)
Study Design Bibliometric analysis. Objective Anterior cervical discectomy and fusion (ACDF) is a typical surgical method in spine surgery and has progressed significantly in the last several decades. The purpose of this study is to determine how the 100 most-cited original articles on ACDF have been the most influential in this field by identifying and analyzing them. Methods The articles on ACDF were identified by searching the Thomson ISI Web of Science database on 30 May 2022. The 100 most-cited articles were selected according to specific criteria. The data extracted from the articles included title, publication date, total citations, journal name, first author, institutions, and keywords. Results The total number of citations was 13,181, with a mean number of 131.81 ± 100.18. The publication dates ranged from 1994 to 2018. Most of these articles originated in the United States (68%) and were published in the 2000s (32%) and 2010s (48%). Spine published most of the articles (30%), followed by the Journal of Neurosurgery-Spine (16%), Spine Journal (14%), and European Spine Journal (13%). The most prolific author was Dr. Todd J Albert (n = 7), with 1,312 citations. The Texas Back Institute was the most productive institution (n = 10). The keywords ACDF, cervical spine, cervical spine, and fusion showed the highest degree of centrality. Conclusion One hundred top-cited articles on ACDF were identified and analyzed in this study. We demonstrate that ACDF is a growing and popular area of research, with the focus of research varying through timeline trends. This will provide a comprehensive and detailed basis for spine surgeons to make clinical decisions and assimilate the research focus of cervical spine surgery.